Carbon neutral product material, flint glass, and producing method of glass
Patent Information
- Application Number
- JP2023138475
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-03-12
AI Technical Summary
【0027】 本発明によれば、上述した課題を解決したカーボンニュートラル生成物、フリント調ガラス、及びガラスの製造方法を提供できる。
Smart Images

Figure 2025032941000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to carbon neutral products, flint-like glass, and methods for making glass. [Background technology]
[0002] Conventionally, glass bottles have been reused in the form of reuse and recycling, as disclosed in the following Non-Patent Document 1 and Non-Patent Document 2. Specifically, glass bottles can be reused in a form called reuse, in which collected used bottles are washed and reused repeatedly, as disclosed in Non-Patent Document 1. In addition, glass bottles can be reused in a form called recycling, in which cullet obtained by crushing used bottles into small pieces is used to make new glass products such as bottles, as disclosed in Non-Patent Document 2. [Prior art documents] [Non-patent literature]
[0003] [Non-Patent Document 1] Glass Bottle 3R Promotion Council website (https: / / www.glass-3r.jp / learn / reuse.html) [Non-Patent Document 2] Glass Bottle 3R Promotion Council website (https: / / www.glass-3r.jp / learn / recycle.html) Summary of the Invention [Problem to be solved by the invention]
[0004] Here, as described above, in the case where glass bottles are crushed into cullet and reused as a resource for forming glass products, used glass can be utilized to create new glass containers as glass products. However, in consideration of the effective utilization of limited resources, it is preferable to utilize not only used glass but also materials other than glass as materials for manufacturing glass.
[0005] Furthermore, from the viewpoint of environmental problems such as global warming, which have become a concern in recent years, it is desirable to suppress the emission of gases consisting of carbon oxides such as carbon dioxide and carbon monoxide emitted during the manufacture of glass. Meanwhile, most of the glasses provided in the prior art are manufactured by using main raw materials including silica sand as a silicon-based material, soda ash as a sodium-based material, and limestone as a calcium-based material. Therefore, the glasses according to the prior art have a problem in that gases consisting of carbon oxides such as carbon dioxide derived from the main raw materials are emitted as by-products during the manufacturing process.
[0006] Therefore, the present invention aims to provide a carbon-neutral product, flint-like glass, and a method for manufacturing glass, which is formed using recycled materials recycled from materials other than glass and contains glass as a main product while minimizing emissions of by-products such as carbon dioxide derived from the main raw materials. [Means for solving the problem]
[0007] (1) The carbon-neutral product of the present invention is formed using as main raw materials a silicon-based material containing a silicon component, a calcium-based material containing a calcium component, and a sodium-based material containing a sodium component, and at least one of the silicon-based material, the calcium-based material, and the sodium-based material constituting the main raw materials is recycled using a material other than glass, and is characterized in that it comprises a main product made of glass formed by using a material that contains at least a part of a recycled material containing carbon derived from the material, and a by-product made of a gas containing carbon oxides that is generated from the main raw materials and is not substantially newly generated.
[0008] By making the carbon-neutral product of the present invention as described above in (1), it is possible to provide glass that uses, as at least a part of the main raw material, a recycled material recycled using a material other than glass. Furthermore, in the carbon-neutral product of the present invention, the gas generated as a by-product derived from the main raw material contains carbon oxides, but is not substantially newly generated. As a result, the carbon-neutral product of the present invention can minimize the generation of gases containing carbon oxides such as carbon dioxide and carbon monoxide that are substantially newly generated in conjunction with the production of the main product, glass.
[0009] (2) The carbon-neutral product of the present invention may be characterized in that the silicon-based material is partly or entirely made of a recycled material that is regenerated from a plant-derived material.
[0010] By making the carbon-neutral product of the present invention as described above in (2), it is possible to obtain glass, which is the main product, using recycled materials regenerated from plant-derived materials.In addition, since the carbon-neutral product of the present invention uses plants as the raw material for the recycled materials, the carbon oxides such as carbon dioxide reduced by the plants are offset by carbon oxides such as carbon dioxide generated when obtaining glass, which is the main product, and from the viewpoint of carbon neutrality and carbon offset, it is possible to substantially suppress the generation of gases containing newly generated carbon oxides.
[0011] (3) The carbon-neutral product of the present invention may be characterized in that a silicate containing a calcium component is used as part or all of the calcium-based material.
[0012] By making the carbon-neutral product of the present invention as described above in (3), the generation of gases consisting of carbon oxides such as carbon dioxide can be suppressed to the extent that silicate is used as a calcium component-containing material, compared to the case where limestone is used as a calcium-based material as in the conventional technology.
[0013] (4) The carbon-neutral product of the present invention may be characterized in that a silicate containing a sodium component is used as part or all of the sodium-based material.
[0014] By making the carbon-neutral product of the present invention as described above in (4), the generation of gases consisting of carbon oxides such as carbon dioxide can be suppressed to the extent that silicate is used as a material containing a sodium component, compared to the case in which soda ash is used as a sodium-based material as in the conventional technology.
[0015] (5) The flint-like glass of the present invention is a glass having flint attributes, and is formed using glass raw materials including a silicon-based material containing a silicon component, a calcium-based material containing a calcium component, a sodium-based material containing a sodium component, and an iron-based material containing an iron component, wherein the silicon-based material is recycled using a material other than glass and is formed by using a material that contains at least a part of a recycled material containing carbon derived from the material, the calcium-based material and the sodium-based material are formed by using a material that contains at least a part of a silicate containing a calcium component and a silicate containing a sodium component, respectively, and the iron-based material is contained in the glass raw materials in an amount of 0.026 mass% or more and 0.35 mass% or less.
[0016] By making the flint-like glass of the present invention as described above in (5), it is possible to provide flint-like glass having flint attributes while using a recycled material recycled using a material other than glass as at least a part of the main raw material. In addition, in the flint-like glass of the present invention, the gas generated as a by-product derived from the main raw material during the manufacturing process contains carbon oxides, but is not substantially newly generated. As a result, the flint-like glass of the present invention can be made to be capable of minimizing the generation of gases containing carbon oxides such as carbon dioxide and carbon monoxide that are substantially newly generated during the manufacturing process.
[0017] (6) The method for producing glass of the present invention includes a frit preparation step of preparing frits containing a silicon-based material containing a silicon component, a calcium-based material containing a calcium component, and a sodium-based material containing a sodium component as main raw materials, and a glass formation step of obtaining glass by using the frits to create a carbon-neutral product having glass as a main product, wherein the frit preparation step is a step of preparing, as the main raw material, at least one of the silicon-based material, the calcium-based material, and the sodium-based material, which is recycled using a material other than glass and contains at least a recycled material containing carbon derived from the material, and the glass formation step is a step of obtaining the glass by using the main raw material to create, as the carbon-neutral product, a main product made of the glass and a by-product made of a gas containing carbon oxides that is derived from the main raw material and is not substantially newly generated.
[0018] The method for producing glass of the present invention, as described above in (5), makes it possible to produce glass using, as at least a part of the main raw material, a recycled material recycled using a material other than glass. Furthermore, in the method for producing glass of the present invention, the gas produced as a by-product derived from the main raw material contains carbon oxides, but is not substantially newly produced. As a result, the method for producing glass of the present invention can minimize the generation of gases containing carbon oxides such as carbon dioxide and carbon monoxide that are substantially newly produced in association with the production of the main product, glass.
[0019] (7) The method for producing glass of the present invention may be characterized in that the silicon-based material is partly or entirely made of a recycled material that is recycled from a material derived from a plant.
[0020] By configuring the glass manufacturing method of the present invention as described above in (7), it is possible to obtain glass, which is the main product, by using a recycled material recycled from a plant-derived material. Furthermore, since the glass manufacturing method of the present invention uses a plant-based raw material as the recycled material, the carbon oxides such as carbon dioxide reduced by the plant are offset by the carbon oxides such as carbon dioxide generated when obtaining the glass, which is the main product, and from the viewpoint of carbon neutrality and carbon offset, it is possible to substantially suppress the generation of gases containing newly generated carbon oxides.
[0021] (8) The method for producing glass of the present invention may be characterized in that a silicate containing a calcium component is used as a part or all of the calcium-based material.
[0022] The method for producing glass of the present invention, as described above in (8), can suppress the generation of gases composed of carbon oxides such as carbon dioxide by the amount of silicate used as a calcium component, compared to the prior art, which uses limestone as a calcium-based material.
[0023] (9) The method for producing glass of the present invention may be characterized in that a silicate containing a sodium component is used as a part or all of the sodium-based material.
[0024] The method for producing glass of the present invention, as described above in (9), can suppress the generation of gases consisting of carbon oxides such as carbon dioxide, by the amount of silicate used as a material containing a sodium component, compared to the prior art, which uses soda ash as a sodium-based material.
[0025] (10) In the glass manufacturing method of the present invention, in the glass frit preparation step, it is preferable that the glass frits prepared include an iron-based material containing an iron component in a range of 0.026 mass% or more and 0.35 mass% or less, a silicon-based material that is partly or entirely regenerated using a material other than glass, a calcium-based material that is partly or entirely a silicate containing a calcium component, and a sodium-based material that is partly or entirely a silicate containing a sodium component.
[0026] The glass manufacturing method of the present invention, by employing the method described above in (10), can produce flint-like glass having the attributes of flint while containing an amount of iron component sufficient to produce amber glass, for example, in the case of producing glass using silica sand as the silicon-based material and carbonates as the calcium-based material and sodium-based material. Effect of the Invention
[0027] According to the present invention, it is possible to provide a carbon-neutral product, a flint-like glass, and a method for producing glass that solve the above-mentioned problems. [Brief description of the drawings]
[0028] [Figure 1] 4 is a photograph showing the results of investigating the colors exhibited in the early stages of melting for RK1 according to an embodiment of the present invention and CH1 according to a comparative example. [Diagram 2] 1 is a photograph showing the results of investigating the colors exhibited in the early stages of melting for RK2 according to an embodiment of the present invention and CH2 according to a comparative example. [Diagram 3] 1 is a photograph showing the results of investigating the colors exhibited in the early stages of melting for RK3 according to an embodiment of the present invention and CH3 according to a comparative example. [Figure 4] 4 is a photograph showing the results of investigating the colors exhibited in the early stages of melting for RK4 according to an embodiment of the present invention and CH5 according to a comparative example. [Diagram 5]1 is a photograph showing the appearance of glasses according to examples of the present invention, RK1-A, RK1-B, RK1-C, RK1-D, CH1-A, CH1-B, CH1-C, and CH1-D. [Figure 6] Photographs (a) and (b) show the appearance of conventional amber glass 1 and 2, respectively. Photographs (c) and (d) show the appearance of samples according to CH1-2 and RK4-2, respectively. Photographs (e) and (f) show the state of the glass samples according to CH1-2 and RK4-2, respectively, adhered to a crucible after melting. [Figure 7] 1 is a graph showing the results of investigating the transmission spectra of samples related to conventionally known amber glass 1, 2, CH1-2, and RK4-2. [Figure 8] 1 is a graph showing the results of measuring the transmission spectrum to evaluate amber absorption for glasses RK1 to RK4 according to examples of the present invention. [Figure 9] 1 is a graph showing the results of measuring the transmission spectrum to evaluate amber absorption for glasses according to comparative examples CH1 to CH4. [Figure 10] 13 is a graph showing the results of amber absorption intensities derived for RK1 to RK4 according to an embodiment of the present invention. [Figure 11] 13 is a graph showing the results of deriving the absorption intensity of amber color for CH1 to CH4 according to the comparative example. [Figure 12] 1 is a graph plotting the results of amber absorption intensity calculated based on the formula described in [Mathematical formula 1] for glasses according to RK1 to RK4 and CH1 to CH4. [Figure 13] Photographs (a) to (c) are external appearance photographs of samples according to CH1-3 to CH1-5, (d) to (e) are external appearance photographs of samples according to RK4-3 to RK4-5, (g) is a photograph showing the external appearance of a conventionally known amber glass, and (h) and (i) are photographs showing the state of the glass samples according to RK4-3 and RK4-2, respectively, adhered to a crucible after melting the glass. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] Hereinafter, a carbon-neutral product and a method for producing glass according to one embodiment of the present invention will be described.
[0030] <About carbon neutral products> The carbon-neutral product is composed of a plurality of products including a main product and a by-product. The carbon-neutral product of this embodiment is one that contains glass as the main product. The carbon-neutral product of this embodiment also contains by-products that are made of gases containing carbon oxides such as carbon dioxide and carbon monoxide that are generated in conjunction with the production of the glass that is the main product.
[0031] The main product, glass, is formed using glass raw materials including main raw materials made of multiple materials. In this embodiment, multiple materials including a silicon-based material, a calcium-based material, and a sodium-based material are used as the main raw materials, and the main product, glass, is formed by using these main raw materials.
[0032] Silicon-based materials are materials that contain silicon components. The silicon-based materials used as the main raw material may be partially or entirely made of recycled materials containing silicon dioxide (SiO2) recycled from materials other than glass. Specifically, the silicon-based materials may be, for example, recycled materials derived from grains such as rice husks, corn husks, and peanut husks (grain-derived recycled materials), recycled materials derived from plants such as plankton, seaweed, and diatoms (plant-derived recycled materials), recycled materials derived from animals such as birds such as chickens, mammals such as cows and pigs, fish, and shellfish (animal-derived recycled materials), recycled materials derived from steel slag (calumite), zeolite, and construction materials (calcium silicate) (industrially derived recycled materials), and other recycled materials that contain silicon components and are recycled from materials other than glass.
[0033] Calcium-based materials are materials that contain calcium components. The calcium-based materials used as the main raw materials can be made of carbonates such as CaCO3 (calcium carbonate: limestone) and Ca(HCO3)2 (calcium bicarbonate) in part or in whole, but it is better to use silicates containing calcium components in part or in whole. Specifically, calcium-based materials that can be suitably used include calcium-based silicates such as CaSiO3 (monoclinic limestone: wallomnite), Ca2SiO4 (β-calcium-silicate dioxide: lahnite), Ca3SiO5 (calcium-silicate trioxide: alite), 3CaO·SiO2 (calcium-silicate trioxide: alite), Ca3SiO5 (calcium-silicate trioxide: alite), CaO·SiO2 (calcium-silicate monoxide: perite), Ca2SiO4 (β-calcium-silicate dioxide: lahnite), 3CaO·2SiO2 (disilica lime trioxide: cellulite), Ca3Si2O7 (disilica lime trioxide: rankinite), and CaO·SiO2 (calcium-silicate monoxide: perite).
[0034] In addition, calcium-based materials can be suitably used as recycled materials regenerated from materials other than glass that contain calcium components, such as shells, dicotyledonous plants such as those from the Solanaceae family, shells (turban shells, scallops), remains of luminous shells using the outer surface of shells, and residues from processing the inner and outer surfaces of shells, buttons (ornaments) made from shells, crustacean shells, and calcium-based materials of biological origin such as food waste (egg shells, animal and fish bones), and industrial-based calcium-based materials such as recycled materials (CaCO3, etc.) regenerated from waste from captured CO2 (generated by CO2 capture technologies such as CCS, CCUS, BEC, BECCS, DAC, DACCS, etc.).
[0035] The sodium-based material is a material that contains a sodium component. The sodium-based material may be made of carbonates such as Na2CO3 (sodium carbonate: soda ash) or NaHCO3 (sodium bicarbonate) as a part or all of the material, but it is preferable to use silicates containing a sodium component as a part or all of the material. Specifically, the sodium-based material may be made of soda silicates (sodium silicates) such as Na2SiO3 (sodium metasilicate), Na4SiO4, Na2Si2O5, or Na2Si4O9.
[0036] In addition, as sodium-based materials, recycled materials regenerated from materials other than glass that contain sodium components, such as waste materials (Na2SO4, NaHSO4, NaHSO3, Na2SO3, Na2S2O4, Na2S2O3) produced by capturing soot and dust from combustion exhaust gas (generated by exhaust gas treatment technology) and recycled materials (Na2CO3, NaHCO3) regenerated from waste materials capturing CO2 (generated by CO2 capture technologies such as CCS, CCUS, BEC, BECCS, DAC, DACCS), can be suitably used.
[0037] As described above, recycled materials can be used as part or all of the silicon-based, calcium-based, and sodium-based materials that are the main raw materials. The recycled materials are not obtained from glass like cullet, but are recycled using materials other than glass. It is preferable to use recycled materials that contain carbon derived from the materials. This allows the carbon contained in the recycled materials to be used as part or all of the carbon used in glass production.
[0038] <About the glass manufacturing method> Next, the method for producing glass according to the present embodiment will be described. The method for producing glass according to the present embodiment is roughly classified into two steps, a glass raw material preparation step and a glass forming step. Each step will be described in more detail below.
[0039] [Glass raw material preparation process] The glass frit preparation step is a step of preparing a glass frit containing a silicon-based material containing a silicon component, a calcium-based material containing a calcium component, and a sodium-based material containing a sodium component as main raw materials. In the glass frit preparation step, at least one of the silicon-based material, the calcium-based material, and the sodium-based material is prepared as a main raw material by regenerating a material other than glass and including at least a part of a recycled material containing carbon derived from the material.
[0040] Here, the above-mentioned recycled materials can be prepared by any appropriate method. For example, when preparing recycled materials derived from grains (grain-derived recycled materials), such as recycled materials derived from rice husks, they can be prepared by the grain-derived recycled material manufacturing method exemplified below.
[0041] The grain-derived recycled material manufacturing method is a manufacturing method that includes, as part or all of the manufacturing process, a step of obtaining grain-derived recycled material containing the silicon component contained in the grain-based raw material as a grain-derived silicon component by heat-treating the grain-based raw material (grain-derived recycled material obtaining step). The grain-derived recycled material manufacturing method can simplify the grain-derived recycled material obtaining step by carrying out the heat treatment of the grain-based raw material in a single stage. Furthermore, the grain-derived recycled material manufacturing method can reduce the content of carbon components generated by the heat treatment of the grain-based raw material by carrying out the heat treatment of the grain-based raw material in multiple stages.
[0042] The grain-derived recycled material obtaining process may be, for example, a process in which heat treatment is performed in two stages, a primary heating process and a secondary heating process. In addition, in the grain-derived recycled material obtaining process, in the primary heating process, a grain-derived raw material made of grain or grain-derived material is heat-treated by direct heating or indirect heating to form a primary heated material, and in the secondary heating process, the primary heated material is indirectly heated. The grain-derived raw material may be directly heated, for example, by igniting and burning the grain-derived raw material in a combustion furnace. In addition, the grain-derived raw material may be indirectly heated, for example, by using a heat treatment device such as a rotary kiln, and the grain-derived raw material may be heated under conditions set so that the temperature inside the furnace is a predetermined temperature. In this way, the organic matter contained in the grain-based raw material can be thermally decomposed in the primary heating process to obtain a primary heated material containing silicon oxide. Even if organic matter remains in the primary heated material without being thermally decomposed, the organic matter can be thermally decomposed and obtained as silicon oxide by further heat treatment in the secondary heating process. In addition, by setting the temperature for the heat treatment in the secondary heating step to a temperature equal to or higher than the combustion temperature of the carbon component contained in the primary heated material, the carbon component contained in the primary heated material can be removed, thereby reducing the content of the carbon component, increasing the purity of the silicon oxide, and suppressing the variation in the content of the carbon component that occurs from lot to lot.
[0043] The glass frit prepared in the glass frit preparation process can be composed of only the above-mentioned main raw materials, or can be composed of the main raw materials plus auxiliary raw materials. Examples of the auxiliary raw materials include Al2O3 (alumina), Fe2O3 (iron oxide (III)), TiO2 (titanium oxide), MgO (magnesium oxide), K2O (potassium oxide), MnO (manganese oxide (II)), BaO (barium oxide), CrO2 (chromium oxide (IV)), Se (metallic selenium), Pt (platinum chloride, platinum), Au (gold chloride, gold), Ag (silver chloride, silver nitrate, silver), H3BO3 (boric acid), K2CO3 (potassium oxide), ZnO (zinc oxide), As(OH)3 (arsenous acid), Sb2O3 (antimony oxide), CaF2 (calcium fluoride), Na2SO4 (sodium sulfate), NaNO3 (sodium nitrate), and C (carbon black).
[0044] In the glass frit preparation step, glass frits can be prepared in the same manner as in the glass manufacturing step in which silica sand, limestone, etc. are used as the main raw materials. Specifically, in the glass frit preparation step, the standard blend ratio is set to 69% to 75% by weight of silicon-based material, 10% to 17% by weight of calcium-based material, and 5% to 15% by weight of sodium-based material, and the blend ratio of each component is varied according to the characteristics of the glass to be manufactured (e.g., viscosity, thermal expansion coefficient, glass transition temperature, melting point, specific gravity, transmittance, color tone, etc.), to blend the glass frits.
[0045] [Glass formation process] The glass forming process is a process for obtaining glass by preparing a carbon-neutral product having glass as a main product using glass frits including the main raw material prepared in the above-mentioned glass frit preparation process. The glass forming process is a process for obtaining glass by preparing a carbon-neutral product including a main product made of glass and a by-product made of a gas containing carbon oxides that is derived from the main raw material and is not substantially newly generated.
[0046] In the glass forming process, the glass raw material containing the main raw material prepared as described above is put into a melting furnace and melted. The melting furnace used in the glass forming process can be a large-scale glass melting furnace such as a Siemens type continuous furnace, or a small-scale tank furnace such as an optical furnace or a hand-blown furnace. A carbon-neutral product can be produced by melting the glass raw material in the melting furnace. That is, glass can be obtained as the main product by removing the melt obtained by melting the glass raw material in the melting furnace from the melting furnace. The glass obtained as the main product can be formed into a shape such as a glass bottle or a glass plate, and then cooled slowly to produce a glass product. In addition, by melting the glass raw material in the melting furnace, a by-product can be obtained that is composed of gases containing carbon oxides such as carbon dioxide and carbon monoxide generated during the production of the main product glass.
[0047] <<Flint-like glass and its manufacturing method>> The flint-like glass of this embodiment is a flint-like glass (glass having flint attributes) with a low amber color concentration. The flint-like glass can be obtained as glass that is the main product in the carbon-neutral product described above. The flint-like glass is obtained by mixing a silicon-based material containing a silicon component, a calcium-based material containing a calcium component, and The glass can be produced by using a glass raw material containing a sodium-based material containing a sodium component as a main raw material and an iron-based material containing an iron component.
[0048] The glass raw material of flint-like glass (hereinafter also referred to as "flint-like glass raw material") is a silicon-based material that is recycled using a material other than glass, and contains at least a part of a recycled material containing carbon derived from the material. The recycled material used for the flint-like glass raw material can be the same as the glass raw material exemplified for the carbon-neutral product described above. In addition, the calcium-based material and the sodium-based material used for the flint-like glass raw material are silicates containing a calcium component and silicates containing a sodium component, respectively. These silicates can also be the same as the glass raw materials exemplified for the carbon-neutral product.
[0049] The flint-like glass raw material contains a plurality of materials including silicon-based materials, calcium-based materials, and sodium-based materials as main raw materials, as well as an iron-based material containing an iron component, similar to the glass raw material of the carbon-neutral product described above. The iron-based material may contain one or more of Fe2O3 (iron (III) oxide / hematite), Fe3O4 (iron (II,III) oxide / magnetite), FeO (iron (II) oxide), etc. The iron-based material may be prepared separately and mixed, but it is also possible to utilize the iron contained as an impurity in rice husks, silica sand, limestone, and glass cullet as a supply source for part or all of the iron-based material. The iron-based material used in the flint-like glass raw material may be contained in the flint-like glass raw material in a range of 0.026 mass% to 0.35 mass%.
[0050] The method for producing the flint-like glass may be the same as the method for producing the glass as the main product of the carbon-neutral product described above. That is, in the method for producing the flint-like glass, the above-mentioned flint-like glass raw material is prepared in the glass raw material preparation step, and glass is formed using the flint-like glass raw material in the glass formation step. EXAMPLES
[0051] Next, an example of the carbon-neutral product and the method for producing glass according to one embodiment of the present invention will be described. In this example, as shown in Table 1 below, four samples consisting of RK1 to RK4 were prepared as examples of the main product of the carbon-neutral product. RK1 to RK4 were formed by selecting the silicon-based material, calcium-based material, and sodium-based material as the main raw materials as shown in Table 1, and obtaining glass as the main product of the carbon-neutral product by the method for producing glass according to the above embodiment.
[0052] Specifically, all of the samples RK1 to RK4 use rice husk-derived recycled materials (grain-derived recycled materials) as the silicon-based material that constitutes the main raw material. Therefore, RK1 to RK4 are formed using silicon dioxide (SiO2) and carbon (C) derived from rice husks as the silicon-based material that constitutes the main raw material. RK1 is formed using CaCO3 (calcium carbonate: limestone) as the calcium-based material that constitutes the main raw material, and Na2CO3 (sodium carbonate: soda ash) as the sodium component. RK2 is formed using CaCO3 (calcium carbonate: limestone) as the calcium-based material that constitutes the main raw material, and Na2SiO3 (sodium metasilicate) as the sodium component. RK3 is formed using CaSiO3 (monoclinic calcium silicate: wallomnite) as the calcium-based material that constitutes the main raw material, and Na2CO3 (sodium carbonate: soda ash) as the sodium component. RK4 was formed using CaSiO3 (monoclinic calc-silica: wallomnite) as the calcium-based material that constitutes the main raw material, and Na2SiO3 (sodium metasilicate) as the sodium component. The glass compositions of RK1 to RK4 were as shown in Table 1.
[0053] In this embodiment, four samples, CH1 to CH4, were prepared as comparative examples. The glasses CH1 to CH4 were formed by selecting the silicon-based material, calcium-based material, and sodium-based material as main raw materials as shown in Table 1, and by the same manufacturing method for glasses as RK1 to RK4.
[0054] Specifically, all of the samples CH1 to CH4 use silica sand (SiO2) from Chemerton as the silicon-based material that constitutes the main raw material. Therefore, CH1 to CH4 are formed using silicon-based materials that do not contain carbon (C) as the main raw material. CH1 is formed using CaCO3 (calcium carbonate: limestone) as the calcium-based material that constitutes the main raw material and Na2CO3 (sodium carbonate: soda ash) as the sodium component. CH2 is formed using CaCO3 (calcium carbonate: limestone) as the calcium-based material that constitutes the main raw material and Na2SiO3 (sodium metasilicate) as the sodium component. CH3 is formed using CaSiO3 (monoclinic calc-silica: wallomnite) as the calcium-based material that constitutes the main raw material and Na2CO3 (sodium carbonate: soda ash) as the sodium component. CH4 was formed using CaSiO3 (monoclinic calc-silica: wallomnite) as the calcium-based material that constitutes the main raw material, and Na2SiO3 (sodium metasilicate) as the sodium component. The glass compositions of CH1 to CH4 are as shown in Table 1.
[0055] [Table 1]
[0056] In the above-mentioned samples RK1 to RK4 and CH1 to CH4, the recycled material derived from rice husk and the silica sand from Chemerton were added as SiO2 sources to the glass raw materials. In each of the above samples, Na2SiO3 (sodium metasilicate) and Na2CO3 (sodium carbonate: soda ash) were added as Na2O sources to the glass raw materials. In each of the above samples, CaCO3 (calcium carbonate: limestone) and CaSiO3 (monoclinic limestone: wallomnite) were added as CaO sources to the glass raw materials. In each of the above samples, Na2SO4 (mirabilite) was added as a sulfur source to the glass raw materials. The amount (content) of Na2SO4 was set so that the ratio of Na2SO4 to the amount of SiO2 (1t-SiO2) ([Na2SO4] / [SiO2]) was 15 kg / t-SiO2. In this embodiment, carbon was added as a reducing agent, and the raw material addition rate was changed as an index of the degree of reduction. In addition, in the above-mentioned samples CH1 to CH4, Fe2O3 was added in an amount within a range that is assumed to make the glass obtained by the above-mentioned manufacturing method colorless and transparent (flint). In the above-mentioned samples RK1 to RK4, Fe2O3 was added in an amount similar to that (same order of magnitude) used to manufacture conventionally known flint glass, as in the samples CH1 to CH4.
[0057] The above-mentioned samples RK1 to RK4 and CH1 to CH4 are all raw material blends designed to produce flint glass. In particular, the content of Fe2O3 in the glass raw materials of the samples RK1 to RK4 and CH1 to CH4 is sufficiently small (small on the order of magnitude) compared to the content of Fe2O3 in the glass raw materials used to manufacture amber glass (approximately 0.22 mass% in the example described below). The blending amount (content) of Na2SO4 (Milk salt / sodium sulfate) which functions as an oxidizing agent among the glass raw materials was set so that the blending ratio of Na2SO4 ([Na2SO4] / [SiO2]) to the blending amount of SiO2 of 1 ton (1t-SiO2) was 15 kg / t-SiO2, as described above. Moreover, among the substances contained in the glass raw materials, the blending amount (content) of carbon (C) functioning as a reducing agent was set to be [C] / ([C]+[Na2SO4])=6.25 mass%, which is the C content when the sum of C and Na2SO4 is 100, unless otherwise specified in the following explanation.
[0058] The above-mentioned samples RK1 to RK4 and CH1 to CH4 were examined for the colors they exhibited in the early stages of melting. The results are shown in Figures 1 to 4. Figures 1 to 4 show the colors of the samples RK1 to RK4 and CH1 to CH4 at 10 minutes, 20 minutes, and 30 minutes after the start of melting.
[0059] Figure 1 compares RK1 and CH1. RK1 and CH1 have in common that they both use CaCO3 (calcium carbonate: limestone) as the calcium-based material and Na2CO3 (sodium carbonate: soda ash) as the sodium-based material, but they differ in that RK1 uses recycled material derived from rice husks (grain-derived recycled material) as the silicon-based material, while CH1 uses silica sand (SiO2) from Chemerton. Comparing the colors exhibited by these samples at the early stage of melting, it was found that CH1, which uses recycled material derived from rice husks, is almost colorless and transparent (flint), while RK1 shows a stronger brownish-brown (amber) color than CH1.
[0060] Figure 2 compares RK2 and CH2. RK2 and CH2 have in common that they both use CaCO3 (calcium carbonate: limestone) as the calcium-based material and Na2SiO3 (sodium metasilicate) as the sodium component. On the other hand, RK2 and CH2 differ in that RK2 uses rice husk-derived recycled material (grain-derived recycled material) as the silicon-based material, while CH2 uses Chemerton silica sand (SiO2). RK2 and CH2 had a stronger brown (amber) color than the above-mentioned RK1 and CH1, respectively.
[0061] Figure 3 compares RK3 and CH3. RK3 and CH3 have in common that they both use CaSiO3 (monoclinic calc-silicate: wallomnite) as the calcium-based material and Na2CO3 (sodium carbonate: soda ash) as the sodium component. On the other hand, RK3 and CH3 differ in that RK3 uses rice husk-derived recycled material (grain-derived recycled material) as the silicon-based material, while CH3 uses Chemerton silica sand (SiO2). RK3 has a slightly stronger brown (amber) color compared to RK1 mentioned above. On the other hand, CH3 is almost colorless and transparent (flint) like CH1 mentioned above.
[0062] Figure 4 compares RK4 and CH4. RK4 and CH4 have in common that they both use CaSiO3 (monoclinic calc-silica: wallomnite) as the calcium-based material and Na2SiO3 (sodium metasilicate) as the sodium component. In other words, RK4 and CH4 use silicates for both the calcium-based material and the sodium-based material. RK4 and CH4 differ in that RK3 uses rice husk-derived recycled material (grain-derived recycled material) as the silicon-based material, while CH3 uses silica sand (SiO2) from Chemerton. Both RK4 and CH4 were almost colorless and transparent (flint) like CH1 mentioned above.
[0063] As described above, the test results of investigating the color exhibited in the early stage of melting for samples related to RK1-RK4 and CH1-CH4 showed that by using rice husk-derived recycled material (grain-derived recycled material) as the SiO2 source, a brownish-brown (amber) color was strongly expressed. In addition, the test results showed that, while a brownish-brown (amber) color was expressed when silicic acid was used as either the Na2O source or the CaO source and a carbonate was used as the other, a brownish-brown (amber) color was not easily expressed when silicic acid was used as both the Na2O source and the CaO source, and the color tended to be colorless and transparent (flint).
[0064] Here, Fe2O3 (iron oxide) contained in the glass raw material has a property of giving a green or brown hue to the glass. Therefore, when producing amber glass, the amount (content) of Fe2O3 (iron oxide) in the glass raw material may be adjusted as an amber coloring factor, similar to C (carbon). On the other hand, as described above, the inventors have conducted extensive research and found that under conditions where a rice husk-derived recycled material (grain-derived recycled material) is used as the SiO2 source and silicic acid is used as both the Na2O source and the CaO source, even if Fe2O3 is mixed in the same amount (0.20 to 0.35 mass%) of Fe2O3 (iron oxide) mixed to obtain amber glass under conditions where silica sand is used as the SiO2 source and carbonate is used as both the Na2O source and the CaO source, a brownish-brown (amber) hue is unlikely to appear, and a flint-like glass (glass having flint attributes) can be obtained even with a mixing amount (content) in the range of 0.026 mass% to 0.35 mass%.
[0065] Based on this knowledge, in this embodiment, as shown in Table 2 below, among RK1 to RK4 and CH1 to CH4, CH1 and RK4 from which flint glass was obtained were used as the standard, and samples having the same C (carbon) content (same order) as CH1 and RK4 but with an order of magnitude larger Fe2O3 (iron oxide) content were prepared as CH1-2 and RK4-2 by the same method as CH1 and RK4, and the color of the glass of the samples was examined. In this embodiment, the Fe2O3 (iron oxide) content in CH1 and RK4 was 0.0257 mass% and 0.0141 mass%, respectively, while the Fe2O3 (iron oxide) content in CH1-2 and RK4-2 was 0.22 mass%, which is within the above-mentioned range of 0.026 mass% to 0.35 mass% (0.20 mass% to 0.35 mass%). As comparative examples, conventionally known amber glasses 1 and 2 were prepared.
[0066] [Table 2]
[0067] As shown in FIG. 6, the sample according to CH1-2 exhibited a deep brownish-brown color (amber) similar to the conventionally known amber glasses 1 and 2 prepared as comparative examples. Considering that the sample according to CH1 is a flint glass, it can be understood that the incorporation of 0.22 mass% Fe2O3 (iron oxide) has the effect of increasing the intensity of the amber color. Therefore, it can be understood that the amount (content) of Fe2O3 (iron oxide) to be incorporated in order to obtain amber glass under the conditions of using silica sand as the SiO2 source and using carbonates as both the Na2O source and the CaO source is appropriate to be in the range of 0.026 mass% to 0.35 mass% (0.20 mass% to 0.35 mass%).
[0068] In contrast, the sample according to RK4-2 (see FIG. 6(d)) had a lower amber color density and was flint-like (having flint attributes) compared to the sample according to CH1-2 (see FIG. 6(c)). As a result, it was found that in the case of using rice husk-derived recycled material (grain-derived recycled material) as the SiO2 source and using silicic acid as both the Na2O source and the CaO source as in the sample according to RK4-2, even if 0.22 mass% of Fe2O3 (iron oxide) is blended as in CH1-2, the amber color density of the glass is suppressed from increasing, and flint-like glass (glass having flint attributes) can be produced. In addition, the transmission spectra of the samples according to the conventionally known amber glasses 1 and 2, CH1-2, and RK4-2 were examined, and the graph shown in FIG. 7 was obtained. From this result, it was found that the transmittance at around 410 [nm], which is the absorption wavelength of amber, of the sample according to RK4-2 is higher than that of the samples according to amber glasses 1 and 2 and CH1-2. This proves that the sample related to RK4-2 is a flint-like glass (glass having the attributes of flint). These results support that under conditions where rice husk-derived recycled material (grain-derived recycled material) is used as the SiO2 source and silicic acid is used as both the Na2O source and the CaO source, by setting the amount (content) of Fe2O3 (iron oxide) to 0.20 to 0.35 mass%, it is possible to obtain a flint-like glass having the attributes (characteristics) of flint, with less tendency to develop a brownish-brown (amber) color.
[0069] In addition, in consideration of the findings obtained based on the test results of CH1, CH1-2, RK4, and RK4-2 described above, samples CH1-3 to CH1-5 and RK4-3 to RK4-5 were prepared that have an order of magnitude larger amount (content) of Fe2O3 (iron oxide) than RK1 and CH4, and have a different amount (content) of C (carbon) than RK1 and CH4. All of these samples have a uniform amount (content) of Fe2O3 (iron oxide) within the above-mentioned range of 0.026 mass% to 0.35 mass% (0.20 mass% to 0.35 mass%). Specifically, all of CH1-3 to CH1-5 and RK4-3 to RK4-5 were prepared with a uniform amount (content) of Fe2O3 (iron oxide) of 0.275 mass%. CH1-3 to CH1-5 were prepared with C (carbon) amounts (contents) of 0.195 mass%, 0.234 mass%, and 0.312 mass%, respectively. RK4-3 to RK1-5 were prepared with C (carbon) amounts (contents) of 0.312 mass%, 0.525 mass%, and 0.700 mass%, respectively. Appearance photographs of these samples are shown in FIG. 13.
[0070] As can be seen from FIG. 13, RK4-3 to RK4-5, which use a rice husk-derived recycled material (grain-derived recycled material) as the SiO2 source and silicic acid as both the Na2O source and the CaO source, were found to be light-colored and flint-like glass, compared with CH1-3 to CH1-5, which use silica sand as the SiO2 source and carbonates as the Na2O source and the CaO source. Also, sample CH1-5, which uses silica sand as the SiO2 source and carbonates as the Na2O source and the CaO source, became amber-colored glass, whereas RK4-3, which contains the same amount of C (carbon) as CH1-5, became colorless and highly transparent flint-colored glass. Therefore, it was found that by using silica sand as the SiO2 source and carbonates as the Na2O source and the CaO source, the coloring effect of iron-based components and carbon-based components, which are coloring factors in glass production, is reduced, and it functions extremely effectively in producing amber-colored glass.
[0071] There are various possible reasons why the above-mentioned results were obtained. However, it is highly likely that the results are due to the fact that, as in the above-mentioned RK4 and RK4-2, a rice husk-derived recycled material (grain-derived recycled material) is used as the SiO2 source, and silicic acid is used as both the Na2O source and the CaO source, and the composition of the glass raw materials changes during the melting process of the glass raw materials, causing the change in the redox degree to behave differently compared to that in conventional glasses such as CH1.
[0072] Here, when cullet obtained by collecting and crushing used glass is used to manufacture new glass as in conventional glass recycling, there is a concern that the presence of impurities contained in the collected glass may adversely affect the quality of glass manufactured using the cullet. For example, iron contained in the cullet and carbon derived from paper labels and plastic labels are coloring factors in glass manufacturing and may be impurities that adversely affect the manufacturing of glass having flint characteristics. Therefore, in the conventional technology of recycling glass resources using cullet, there is a problem that the amount of cullet used when manufacturing flint-like glass is limited, making it difficult to increase the recycling rate. However, as described above, by using a rice husk-derived recycled material (grain-derived recycled material) as the SiO2 source and silicic acid as both the Na2O source and the CaO source, and using silica sand as the SiO2 source and carbonates as the Na2O source and the CaO source, flint-like glass can be manufactured even when many iron-based materials and carbon (carbon) that would result in amber glass are blended. Therefore, by using rice husk-derived recycled material (grain-derived recycled material) as the SiO2 source and silicic acid as both the Na2O source and the CaO source, flint-like glass can be produced even if the usage rate of cullet in the glass raw material is increased, which contributes to improving the recycling rate of glass.
[0073] In addition, as in RK4 and RK4-2, by using a rice husk-derived recycled material (grain-derived recycled material) as the SiO2 source and silicic acid as both the Na2O source and the CaO source, it is possible to suppress the function of C (carbon) and Fe2O3 (iron oxide) as amber coloring factors, and it is therefore considered possible to manufacture flint-like glass (flint attribute glass) that has other functions obtained by blending C and Fe2O3. For example, glasses such as RK4 and RK4-2 are flint-like glasses (flint attribute glasses), but are expected to exhibit high performance in some or all of the functions expressed by the presence of Fe2O3, such as ultraviolet absorption function, infrared absorption function, corrosion resistance, and chemical stability, compared to conventionally known flint glasses. In addition, since C (carbon) in the glass raw material expresses the desulfurization effect that is expressed during the manufacturing process, glasses such as RK4 and RK4-2 are flint-like glasses (flint attribute glasses), but are expected to have a low sulfur content and high transparency and mechanical properties compared to conventional flint glasses.
[0074] Here, in order to investigate the effect on the color of glass by varying the blending amount (content) of carbon (C) which functions as a reducing agent in the glass raw material, among the above-mentioned samples RK1 to RK4 and CH1 to CH4, RK1 and CH1 were used as the standard, and the raw materials other than carbon contained in the glass raw material were the same as those of RK1 and CH1, and samples RK1-A to RK1-D and CH1-A to CH1-D were created by changing the C content ([C] / [SiO2] mass%) calculated from the weight of C relative to the weight of SiO2 alone in the raw material. The results are shown in Figure 5.
[0075] 5, the samples RK1-A to RK1-D (RK1-based samples) have the same raw materials as RK1 except for carbon contained in the glass raw material, and the C content ([C] / [SiO2]mass%) calculated from the weight of C relative to the weight of SiO2 alone in the raw material is 0.015, 0.050, 0.075, and 0.100 mass%, respectively. Also, the samples CH1-A to CH1-D (CH1-based samples) have the same raw materials as CH1 except for carbon contained in the glass raw material, and the C content ([C] / [SiO2]mass%) calculated from the weight of C relative to the weight of SiO2 alone in the raw material is 0.13, 0.17, 0.205, and 0.23 mass%, respectively. The glass for the RK1 and CH1 samples was prepared by melting the batches at 1,450 degrees Celsius for one to two hours, casting, and then slowly cooling at 570 degrees Celsius for one hour. The glass was then ground and polished to a size of approximately 22 mm x 22 mm x 10 mm.
[0076] As can be seen from the results shown in FIG. 5, it was found that in both the CH1 and RK1 samples, the amber color tends to become stronger when the carbon ratio is increased. In addition, when the carbon content is similar in the CH1 and RK1 samples and RK1-D is compared with CH1-A, it was confirmed that RK1-D tends to have a stronger amber color than CH1-A. Therefore, under the condition where carbonates are used as both the Na2O source and the CaO source, when a rice husk-derived recycled material (grain-derived recycled material) is used as the SiO2 source as in the RK1 sample, the amber color tends to become stronger compared to when silica sand is used as the SiO2 source as in the CH1 sample. On the other hand, considering that the above-mentioned sample related to RK4 is a flint-like glass, it can be seen that the characteristic of strengthening the amber color due to the rice husk-derived recycled material is suppressed by using silicate as both the Na2O source and the CaO source, even when a rice husk-derived recycled material (grain-derived recycled material) is used as the SiO2 source. Therefore, when using recycled materials derived from rice husks (grain-derived recycled materials) as a SiO2 source, it was found that if a flint-like glass is desired, it is best to use silicates as both the Na2O source and the CaO source, and if an amber-like glass is desired, it is best to use carbonates as both the Na2O source and the CaO source.
[0077] 8 and 9 show transmission spectra measured for the glasses CH1 to CH4 and RK1 to RK4 in FIG. 5, respectively, in order to evaluate amber absorption (light absorption characteristic specific to amber-colored glass). As shown in FIG. 8, when comparing the absorbance curves of the glasses CH1 to CH4, it was found that the transmittance at the amber absorption wavelength of 410 [nm] decreased as the amount of carbon added increased. Similarly, as shown in FIG. 9, when comparing the absorbance curves of the glasses RH1 to RH4, it was found that the transmittance at the amber absorption wavelength of 410 [nm] decreased as the amount of carbon added increased. This confirmed that for both samples using Chemerton silica sand (SiO2) such as CH1 to CH4 and samples using rice husk-derived recycled material (grain-derived recycled material) such as RK1 to RK4, the amber color became stronger as the amount of C (carbon) in the glass raw material increased, regardless of whether silicate was used as the Na2O source or CaO source.
[0078] For the glasses RK1 to RK4 and CH1 to CH4 shown in FIG. 5, the absorption intensity of amber color was derived based on the formula described in the following [Mathematical formula 1]. The results for the glasses RK1 to RK4 are shown in FIG. 10, and the results for the glasses CH1 to CH4 are shown in FIG. 11. In addition, using the wavelength λ1 at which the transmittance is minimum in the wavelength range of 400 to 430 [nm] and the wavelength λ2 at which the transmittance is maximum in the wavelength range of 470 to 700 [nm], ΔA'=2.303·ΔA / d=2.303·(A1-A2) / d (d: sample thickness) calculated from the absorbances A1 and A2 at each of these wavelengths was used as an index of the intensity of amber absorption. This ΔA' coincides with the absorption coefficient of amber in an ideal state where scattering and reflection are the same at λ1 and λ2, and there is only amber absorption at λ1 and no absorption at λ2. Figure 12 shows a graph plotting the ΔA' of glass produced from a batch using rice husk-derived recycled material (rice husk ash / grain-derived recycled material) as the SiO2 source and the ΔA' of glass produced from a batch using silica sand against the amount of carbon added.
[0079]
number
[0080] As can be seen by comparing FIG. 10 and FIG. 11, it was found that the increase rate of the absorption intensity of amber color in RK1 to RK4 (the increase amount of the absorption intensity of amber color with respect to the increase of the carbon amount) is more gradual than the increase rate of the absorption intensity of amber color in CH1 to CH4. Based on this result, it was found that by using a material containing carbon derived from recycled materials, such as SiO2 (silicon oxide) derived from rice husks, as a constituent material of the main raw material as in RK1 to RK4, it is possible to suppress the intensity of amber color from fluctuating sharply with the increase amount of carbon, compared to the case where the main raw material is composed of a material not containing carbon derived from recycled materials as in CH1 to CH4. As a result, even if a material whose carbon content is expected to vary depending on the lot or the raw material of the recycled material, such as SiO2 (silicon oxide) derived from rice husks, is used as a constituent material of the main raw material, it is possible to suppress the intensity of amber color in the produced glass from fluctuating with a large range.
[0081] In both cases of CH1 to CH4 shown in FIG. 10 and RK1 to RK4 shown in FIG. 11, it was found that the rate of increase in the absorption intensity of amber color was the most gentle when both the calcium component and the sodium component constituting the main raw material were silicates. In addition, in both cases of CH1 to CH4 shown in FIG. 10 and RK1 to RK4 shown in FIG. 11, it was found that the rate of increase in the absorption intensity of amber color was gentler when the calcium component was silicate and the sodium component was carbonate than when the calcium component was carbonate and the sodium component was silicate. Therefore, it was found that the rate of increase in the absorption intensity of amber color can be made gentler by preferentially changing the calcium component constituting the main raw material to silicate over the sodium component. [Industrial Applicability]
[0082] The present invention is suitably applicable to the production of carbon-neutral products using recycled materials recycled from materials other than glass, as well as glass, which is the main product of the carbon-neutral products, and flint-like glass.
Claims
1. A silicon-based material containing a silicon component; A calcium-based material containing a calcium component; A sodium-based material containing a sodium component; It is formed from the main ingredient, At least one of the silicon-based material, the calcium-based material, and the sodium-based material constituting the main raw materials is recycled using a material other than glass, and the main product is made of glass formed by using a material that contains at least a part of a recycled material containing carbon derived from the material; a by-product comprising a gas containing carbon oxides that is generated from the main raw material and is not substantially newly generated; A carbon-neutral product comprising:
2. The carbon-neutral product according to claim 1 , characterized in that the silicon-based material is partly or entirely made of recycled material regenerated from materials derived from plants.
3. 3. The carbon-neutral product according to claim 1 or 2, characterized in that a silicate containing a calcium component is used as part or all of the calcium-based material.
4. 3. The carbon-neutral product according to claim 1 or 2, characterized in that a silicate containing a sodium component is used as part or all of the sodium-based material.
5. A flint-like glass having flint properties, A silicon-based material containing a silicon component; A calcium-based material containing a calcium component; A sodium-based material containing a sodium component; An iron-based material containing an iron component; The glass is formed using a glass raw material comprising The silicon-based material is formed by using a material other than glass that is recycled and contains at least a part of a recycled material containing carbon derived from the material, the calcium-based material and the sodium-based material are formed by using materials that contain, at least in part, a silicate containing a calcium component and a silicate containing a sodium component, respectively; The flint-like glass is characterized in that the iron-based material is contained in the glass raw material in an amount of 0.026 mass% or more and 0.35 mass% or less.
6. A glass frit preparation step of preparing a glass frit including a silicon-based material containing a silicon component, a calcium-based material containing a calcium component, and a sodium-based material containing a sodium component as main raw materials; a glass forming step of producing a carbon-neutral product having glass as a main product by using the glass raw material to obtain glass; having The glass frit preparation step comprises: preparing, as the main raw material, at least any one of the silicon-based material, the calcium-based material, and the sodium-based material that is recycled using a material other than glass and that contains at least a recycled material containing carbon derived from the material; The glass forming step comprises: a process for producing the glass by using the main raw material to produce, as the carbon-neutral product, a main product made of the glass and a by-product made of a gas containing carbon oxides that is derived from the main raw material and is not substantially newly produced, thereby obtaining the glass.
7. 7. The method for producing glass according to claim 6, wherein the silicon-based material is partly or entirely made of a recycled material that is recycled from a material derived from a plant.
8. 8. The method for producing glass according to claim 6, wherein a silicate containing a calcium component is used as a part or all of the calcium-based material.
9. 8. The method for producing glass according to claim 6, wherein a silicate containing a sodium component is used as a part or the whole of the sodium-based material.
10. 8. The method for producing glass according to claim 6 or 7, characterized in that in the glass frit preparation step, the glass frit includes an iron-based material containing an iron component in a range of 0.026 mass% to 0.35 mass%, a silicon-based material that is partly or entirely regenerated using a material other than glass, a calcium-based material that is partly or entirely silicate containing a calcium component, and a sodium-based material that is partly or entirely silicate containing a sodium component are prepared.
Citation Information
Patent Citations
Production of synthetic silicate and its use in production of glass
JP1998218638A
Method for preparing batch materials for glass production
JP2005504709A
Glass, and method for manufacturing glass
JP2023018414A
Methods of making glass from organic waste food streams
US20150065329A1